PENGARUH PENERAPAN METODE PROBLEM SOLVING TERHADAP PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IX MTsN 8 PESISIR SELATAN TAHUN PELAJARAN 2018/2019 - Ekaputri, Yanti Nazmai (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
This research is motivated by the low learning outcomes of students of class IX MTsN 8 Pesisir Selatan. This study aims to determine whether the learning outcomes of the problem solving abilities of class IX students of MTsN 8 Pesisir Selatan who apply the Problem Solving method are better than learning outcomes on the problem solving abilities of students who apply conventional learning. This type of research is experimental research, with a randomized study design on the subject. The population in this study were students of class IX MTsN 8 Pesisir Selatan which consisted of 3 classes. The sampling technique used was random, which was chosen as the sample class is IX.1 as the experimental class and IX.2 as the control class. The instrument used in this study was a test of problem solving ability. The form of the test used is the form of essays with the reliability of the test is r_11 = 0.88. The data analysis technique used is the one-party t test with the help of SPSS Software. Based on the results of data analysis, it is known that both sample classes are normally distributed and homogeneous at the level of confidence α = 0.05 and the results of the hypothesis test obtained P-value equal to 0,000, which means less than α = 0.05, the hypothesis in this study was accepted. So it can be concluded that the learning outcomes of students 'problem solving abilities by applying problem solving methods are better than students' problem solving abilities by applying conventional learning in class IX students of MTsN 8 South Coastal Academic Year 2018-2019 with a 95% confidence level.